Atividade enzimatica hidrolítica dos fungos amazônicos pycnoporus sanguineus (l.f.) Murr e panus crinitus (l.ex. Fr.) Singer - Carmo , Cynara da Cruz (2005)
Enzymes of hydrolytic nature such as cellulase, xylanase and glicosidase and/or others agents non-enzymatic produced by wood decay fungi, show a huge biotechnological potential. I order to investigate hydrolytic potential of two amazonian wood decay fungi, Pycnoporus sanguineus (L.:F.) Murr and Panus crinitus (L. Ex. Fr.) Singer, studies on influence of pH, temperature and medium at growth of fungi as well as determination of enzymatic activity of FPA, -glucanase and -xylosidase on stationary and agitation conditions at 180 rpm were done. Fungi studied shown preference by acid conditions (pH optimum 5,0) and temperature optimum between 30- 35° C. P. sanguineus had these optimum conditions at sabouraud medium supplemented with peptone while P. crinitus at malt extract medium. Temperature had more influence on fungal growth. Enzymatic activity were better at agitation conditions. At stationary condition with no glucose in the medium it wasn't detected FPA activity in both fungi and only to P. sanguinues the endo--glucanse activity was detected. At stationary growth the addition of glucose increase about 38% endo--glucanase activity for P. sanguineus but it not contributed to increase this activity for P. crinitus. For both fungi the -xylosidase activity at stationary conditions and presence of glucose it wasn't followed by endo-glucanase activity. P. crinitus presents a greater hemicelulolytic activity become evident by greater -xylosidase activity while P. sanguineus showed great celulolitic activity. There is need studies to find new medium to maximize hydrolytic enzyme activity to get viable purification to possible biotechnological uses.